Research on AI-Driven Data Science Curriculum Construction and Innovative Teaching Models based on the “New Economics and Management” Strategy - Wang, Shenling; Chang, Cai (International Journal of Social Sciences and Public Administration, 2025)
In response to the demand for high-quality compound talents in the digital economy era, China’s higher education system has gradually proposed and promoted the “New Economics and Management” (NEM) strategy, which aims to cultivate professional economic management talents with data thinking, technical application capabilities, and innovation abilities. With the rapid development of technologies such as artificial intelligence (AI), big data, and cloud computing, the current curriculum and teaching models urgently need to be optimized and innovated. This study aims to construct an AI-driven data science curriculum framework adapted to the digital economy era and propose innovative teaching models based on the NEM strategy, leveraging the advantages of AI technology. By analyzing the practical experience of domestic and international universities in AI and data science teaching, this study proposes a comprehensive curriculum design framework that deeply integrates economic management courses with AI technology and data science, and innovatively introduces modern teaching methods such as project-based learning (PBL), flipped classroom, and blended learning. The study shows that these innovative models not only enhance students’ abilities in data analysis, technical application, and innovative thinking, but also, through the concept of interdisciplinary integration, make the curriculum content cover both traditional economic management knowledge and technical application abilities, effectively promoting the cultivation of compound talents. By continuously deepening the application of technology, strengthening the construction of teaching staff, and reinforcing practical teaching, future AI and data science courses will better meet the needs of the digital economy era and make greater contributions to cultivating high-quality compound talents with innovation and technical application abilities.